Performance of stone mastic asphalt incorporating cellulose fiber - Nurul Ain Najwa, Md Fauzi (2019)
Stone mastic asphalt (SMA) is well known as a high coarse aggregate content that interlocks to form a stone skeleton that resist permanent deformation. However, it facing a lot of problems such as rutting and stripping because of the high temperature and repeated axial load (Zulhaidi et al., 2018). It also have creep in different loads and temperatures. The cellulose fibre can improve the viscosity of the unmodified asphalt. Thus, the aim of this study is intended to utilize the cellulose fiber high tensile strength to overcome the problem that is related to SMA. The addition of cellulose fiber into the control asphalt improved the recovery ability of asphalt binder. This paper presents the outcome of a laboratory investigation on Marshall Stability, Resilient Modulus, Dynamic Creep and Cantabro Loss Abrasion of Stone Mastic Asphalt (SMA) that incorporated with cellulose fiber modified binder. Penetration Grade 60-70 (PEN60-70) types of binder were mixed with cellulose fiber of 0%, 0.2%, 0.3%, 0.4%, 0.5% and 0.6% by weight of mixture. The mixtures were tested for Abrasion, Marshall Stability, Resilient Modulus and Dynamic Creep in order to evaluate the performance of modified SMA. From the results, it shows that the existence of cellulose fiber is capable of enhancing the performance of asphalt mixture, and the addition of 0.2% cellulose fiber contributes to lowest value of abrasion,0.4% cellulose fiber produce the high density, while 0.3% producing highest value of resilient modulus and dynamic creep, 0.2% for stability and 0.4% for stiffness. For future study, it is recommended to analyses the physical behaviour of SMA with the existence of cellulose fiber in order to prove its reliability in various applications in asphalt mixture.